How democracies die - Levitsky, Steven; Ziblatt, Daniel, 1972- (Great Britain : Penguin Books, 2019)
"A . . . look at the demise of liberal democracies around the world--and a road map for rescuing our own"--Publisher.
Fateful alliances -- Gatekeeping in America -- The great Republican abdication -- Subverting democracy -- The guardrails of democracy -- The unwritten rules of American politics -- The unraveling -- Trump against the guardrails -- Saving democracy.
Includes bibliographical references (p. 235-290) and index.
Kirkus Review
New York Times
Kirkus Review, December 2017
New York Times, March 2018
Adult.
Keywords: Democracy; Democracy -- United States; Political culture; Political culture -- United States; Democracy; Democracy -- United States; Political science; Political science -- United States; United States -- Politics and government -- 2017-; United States -- Politics and government